2000
DOI: 10.1007/bf02464381
|View full text |Cite
|
Sign up to set email alerts
|

Two new species and one new variety of Agaricales from central Honshu, Japan

Abstract: Two new species and one new variety of Agaricales are described and illustrated from central Honshu, Japan: Clitocybe trogioides var. odorifera var. nov. (subgenus Cystoclitus section Cystoclitus), forming white, infundibuliform basidiomata, was collected from leaf litter in the Quercus-Pasania forests; Gerronema nemorale sp. nov. (section Xanthophylla), forming small, olivaceous, omphalinoid basidiomata, was found on dead fallen twigs in the Quercus-Pasania forests; Psathyrella cineraria sp. nov. (subgenus My… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Its microscopic studies showed that it represents Gerronema nemorale Har. Takah., a fungus recently described as new to science from Honshu, Japan (Takahashi 2000). These collections represent the first published records in the Republic of Korea.…”
Section: Gerronema Nemorale (Basidiomycota Agaricomycetes)mentioning
confidence: 97%
See 1 more Smart Citation
“…Its microscopic studies showed that it represents Gerronema nemorale Har. Takah., a fungus recently described as new to science from Honshu, Japan (Takahashi 2000). These collections represent the first published records in the Republic of Korea.…”
Section: Gerronema Nemorale (Basidiomycota Agaricomycetes)mentioning
confidence: 97%
“…E c o l o g y. Saprotrophic, lignicolous; growing on stems, branches and twigs of Quercus mongolica and an unidentified broadleaved tree. At the type locality in Japan, it was collected in a lowland forest with dominating Pasania edulis, Quercus myrsinaefolia and Ligustrum japonicum (Takahashi 2000). D i s t r i b u t i o n .…”
Section: Gerronema Nemoralementioning
confidence: 99%
“…Morphologically and phylogenetic similar to Coprinopsis jilinensis , C. uliginicola is characterised by long basidiospores of 10–12(–15) µm, pleurocystidia absent and caulocystidia present, pileipellis no encrusting pigment ( Smith 1972 ). Other similar species, C. cineraria is characterised by grey, hygrophanous and striate pileus, little short basidiospores (6.5–8.5 µm), pleurocystidia absent, pileipellis an epithelium ( Takahashi 2000 ); C. melanthina is characterised by little long and subcolourless basidiospores (avl × avw = 10.5 × 5.8 µm), pleurocystidia absent (Kits van Waveren 1985 ); C. pusilla has small basidiomata, grey pileus, subcolourless and verrucose basidiospores (this study) and Psathyrella subagraria has hygrophanous pileus, thick flesh and caulocystidia present ( Smith 1972 ), both of which could be clearly distinguished from C. jilinensis in terms of morphology.…”
Section: Resultsmentioning
confidence: 99%
“… C. uliginicola is characterised by large basidiomata, brown-black basidiospores, pore present ( Smith 1972 ). C. cineraria is characterised by fibrous veil at the edges easily disappearing, smaller basidiospores (6.5–8.5 × 4–5 µm), pileipellis an epithelium ( Takahashi 2000 ).…”
Section: Resultsmentioning
confidence: 99%
“…Clitocybe is a character-poor genus; in fact, many species differ only in very subtle features, such as basidioma macromorphology, pileipellis structure and basidiospores size (e.g. Harmaja 1969;Bigelow 1982Bigelow , 1985Kuyper 1982Kuyper , 1995Clémençon 1984;Singer 1986;Raithelhuber 1990Raithelhuber , 2004Bon 1997;Takahashi 2000Takahashi , 2003Gregory 2007). From a morphological perspective, this often makes species identification difficult or even daunting.…”
Section: Introductionmentioning
confidence: 98%